A New Grid Resource Discovery Framework - Mahamat Issa, Hassan (2009)
Resource discovery (RD) is an important key issue in grid systems since resource reservation and task scheduling are based on it. This paper proposes a novel semantic-based scalable decentralized grid RD framework. The paper integrates ontology, peer-to-peer (P2P) network and intelligent agents to build the framework. The framework consists of an ontology model, an agent model, and a set of algorithms for implementing the P2P architecture and searching the shared resources. The paper shows how the framework satisfies grid RD features such as scalability, decentralization, dynamism and interoperability.